2011
DOI: 10.1007/s00284-011-0003-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Acanthamoeba from Tap Water in Rio Grande do Sul, Brazil

Abstract: A total of 136 samples of tap water were collected from state and municipal schools between March and November 2009. The samples were filtered through cellulose nitrate membranes that were seeded at non-nutrient agar 1.5% containing an overlayer of Escherichia coli suspension. Thirty-one (22.79%) tap water samples investigated were found positive for free-living amoebae (FLA). From these, 13 presented as FLA that seems to belong to the genus Acanthamoeba. All samples of FLA were cloned and identified as belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…On the other hand, similar result (88.9%) was obtained in Qalyubia governorate [23] . In other countries, a low detection rate (9.3%) was recoded in USA [25] , whereas variable rates were reported in several studies all over the world; 46.9% in Korea [26] , 23% in Nicaragua [27] , 22.79% in Brazil [28] , 29.4% and 22% in Turkey [29,30] . However, similar results were obtained on examination of household tap water samples in UK (89%) [31] and in Ohio, USA (79%) [25] .…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, similar result (88.9%) was obtained in Qalyubia governorate [23] . In other countries, a low detection rate (9.3%) was recoded in USA [25] , whereas variable rates were reported in several studies all over the world; 46.9% in Korea [26] , 23% in Nicaragua [27] , 22.79% in Brazil [28] , 29.4% and 22% in Turkey [29,30] . However, similar results were obtained on examination of household tap water samples in UK (89%) [31] and in Ohio, USA (79%) [25] .…”
Section: Discussionmentioning
confidence: 96%
“…Also the contamination rate of drinking water with the amoebae in Taiwan was reported 39.5 % in 2014 (Kao et al 2014). Furthermore, Winck et al (2011), analysed 136 samples of tap water which showed lower contamination rates compared with ours (Winck et al 2011). Due to the limitation in the sampling of drinking water in the public places, additional studies require with more samples.…”
Section: Discussionmentioning
confidence: 99%
“…A temperature tolerance test was also performed for Acanthamoeba : three sets of subculture plates (NNA- E. coli ) for each sample were incubated at 37, 42, and 52°C, respectively. All plates were examined daily for amoebal growth by phase contrast microscopy for seven days [21]. When an FLA strain was isolated, the flagellate transformation test was applied for the identification of N. fowleri [20].…”
Section: Methodsmentioning
confidence: 99%